The Role of the Financial and Administrative Control Bureau in Detecting Financial and Administrative Deviations in Local Authoritie (Mutah Journal of Humanities and Social Sciences (MJHSS), 2024)
This study aimed to identify the role of the Financial and Administrative Control Bureau in detecting aspects of financial and administrative deviations in local authorities. The significance of the study lies in the importance of clarifying the efforts made through the supervisory role of the Financial and Administrative Control Bureau in revealing financial and administrative deviations in the local government sector. To achieve the objectives of the study, the study uses a descriptive, analytical approach by adopting the survey method in conducting 7 interviews with specialists, in addition to employing a purposeful sample by distributing 100 questionnaires to employees in local authorities, besides relying on content analysis. The study reached several results, the most prominent of which was that the role of the Financial and Administrative Control Bureau in detecting financial and administrative deviations in local authorities is insufficient. The study recommended the need of the Financial and Administrative Control Bureau to hold workshops in order to develop the capabilities of the employees of local authorities and to work to assist these employees, especially those in the internal control units, in detecting financial and administrative deviations.
Keywords: Financial and Administrative Control Bureau; Financial and Administrative Deviations; Procedures; Local Authority